(untitled) (SCHOLARS: Journal of Arts & Humanities, 2026)
This article examines subtle acts of widows’ resistance to gain their agency and dignity in Deepa Mehta’s film Water (2005) in the light of the notion of passive resistance developed by M. K. Gandhi. It explores circumstances and instances of subtle acts of resistance mainly by Chuyia, Kalyani and Shakuntala Devi. Resistance, in general, is connected with an explicitly political or social action. However, in this film, widows are engaged in subtle acts of resistance to patriarchy. These understated acts are embedded in widows’ daily routines, gestures and interpersonal relationships. These acts complicate conventional notions of resistance. To illustrate, Karl Marx and Engels consider “the history of hitherto existing society is the history of class struggles” (14). The widows’ subtle acts of resistance in this context surpass any conventional notions of class struggles. This study examines how such quiet forms of defiance emerge, what cultural, religious, and power structures they encounter, and how they extend the theoretical understanding of resistance. By fighting quietly against the authority, the widows claim their agency and dignity. To elucidate this assertion, M.K. Gandhi’s concept of passive resistance has been used. Through this lens, Chuyia’s rejection of widowhood and instinctual resistance, Kalyani’s craving for love and refusal to be commodified, and Shakuntala Devi’s journey from contemplation to quiet rebellion are unraveled. The aforementioned acts of these widows reflect subtle acts of resistance, which help them to live with their freedom and dignity, and even raise awareness among widows to fight against austerity and marginalization.